2008
DOI: 10.1097/mao.0b013e318170b5f8
|View full text |Cite
|
Sign up to set email alerts
|

Serous Otitis Media in Children

Abstract: We observed a high rate of culture positivity for A. otitidis in patients with clinical OME without suppuration. Further studies are needed to confirm whether the association of A. otitidis with OME represents causality. Antibiotic therapy aimed at A. otitidis is complicated by reported resistance, thus emphasizing the importance of our understanding of the pathogenetic role played by this organism

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
(14 reference statements)
2
10
0
Order By: Relevance
“…However, previous in vitro and in vivo studies demonstrated that this bacterium had an immunostimulatory capacity, and this indicated that it was not included in the normal flora of the middle ear cavity (15-21). This suggestion was also supported by de Miguel Martinez et al (12). In their study, A. otitidis was investigated in children with OME and acute otitis media, where the control group had a cochlear implant and did not have otitis for the previous 6 months.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…However, previous in vitro and in vivo studies demonstrated that this bacterium had an immunostimulatory capacity, and this indicated that it was not included in the normal flora of the middle ear cavity (15-21). This suggestion was also supported by de Miguel Martinez et al (12). In their study, A. otitidis was investigated in children with OME and acute otitis media, where the control group had a cochlear implant and did not have otitis for the previous 6 months.…”
Section: Discussionsupporting
confidence: 77%
“…Thus, it can result in developmental impairment of linguistic, behavioral, motor and social skills (1, 11, 12). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When first discovered, A. otitidis was reported not to be found in the EAC (Faden and Dryja, 1989), but both A. otitidis and T. otitidis have since been proposed as members of the normal EAC flora. Both organisms have been observed in the EACs of healthy adults and children (Stroman et al, 2001;Frank et al, 2003;Tano et al, 2008;De Baere et al, 2010), indicating that they are capable of growth in the EAC without causing disease. Given this finding, it becomes important to establish whether the detection of A. otitidis and T. otitidis in MEF is a result of contamination during sampling, or if they inhabit both sites.…”
Section: Why Is the Role Of These Organisms In Otitis Media Still Undmentioning
confidence: 99%